Impact of Irradiation on Vector Competence of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) for Dengue and Chikungunya Viruses - Balestrino, Fabrizio; Bouyer, Jérémy; Vreysen, Marc J. B.; Veronesi, Eva (Frontiers in Bioengineering and Biotechnology, 2022)
Effective control strategies against arthropod disease vectors are amongst the most powerful tools to prevent the spread of vector-borne diseases. The sterile insect technique (SIT) is an effective and sustainable autocidal control method that has recently shown effective population suppression against different Aedes vector species worldwide. The SIT approach for mosquito vectors requires the release of radio-sterilized male mosquitoes only, but currently available sex separation techniques cannot ensure the complete elimination of females resulting in short-term risk of increased biting rate and arboviral disease transmission. In this study, we compared for the first time the transmission of dengue and chikungunya viruses in Aedes aegypti and Aedes albopictus females exposed as pupae to an irradiation dose of 40 Gy. Females of both species were fed on blood spiked with either dengue or chikungunya viruses, and body parts were tested for virus presence by real-time RT-PCR at different time points. No differences were observed in the dissemination efficiency of the dengue virus in irradiated and unirradiated Ae. albopictus and Ae. aegypti mosquitoes. The dissemination of the chikungunya virus was higher in Ae. albopictus than in Ae. Aegypti, and irradiation increased the virus load in both species. However, we did not observe differences in the transmission efficiency for chikungunya (100%) and dengue (8–27%) between mosquito species, and irradiation did not impact transmissibility. Further implications of these results on the epidemiology of vector-borne diseases in the field are discussed.